Chapter Il cantiere di restauro, luogo di formazione e di educazione - MARINO, LUIGI (Firenze University Press, 2025)
Archaeologists and architects: areas of communication, collaboration and conflict: this is the title of a speech by Philip Rahtz that after a few decades can constitute a useful starting point for reflections on the collaborations that can (should) be activated in a restoration site when, not infrequently, the interventions move mainly in accordance with theoretical models that have few and uncertain references with the surviving material traces. On the other hand, excavation campaigns are often carried out without adequate attention to protection actions (preventive, during and after) despite knowing that the excavation will set in motion degenerative mechanisms which in turn will cause other damage which will be aggravated by the state of abandonment in whose sites and monuments will be left behind. The relationships of collaboration and sharing that are established in a restoration site could facilitate the development of a sense of belonging and mutual responsibility.